A proposal for a new PhD level curriculum on quantitative methods for drug development. (9th July 2018) - Jaki, T.; Gordon, A.; Forster, P.; Bijnens, L.; Bornkamp, B.; Brannath, W.; Fontana, R.; Gasparini, M.; Hampson, L.V.; Jacobs, T.; Jones, B.; Paoletti, X.; et al.
Abstract : This paper provides an overview of "Improving Design, Evaluation and Analysis of early drug development Studies" (IDEAS), a European Commission–funded network bringing together leading academic institutions and small‐ to large‐sized pharmaceutical companies to train a cohort of graduate‐level medical statisticians. The network is composed of a diverse mix of public and private sector partners spread across Europe, which will host 14 early‐stage researchers for 36 months. IDEAS training activities are composed of a well‐rounded mixture of specialist methodological components and generic transferable skills. Particular attention is paid to fostering collaborations between researchers and supervisors, which span academia and the private sector. Within this paper, we review existing medical statistics programmes (MSc and PhD) and highlight the training they provide on skills relevant to drug development. Motivated by this review and our experiences with the IDEAS project, we propose a concept for a joint, harmonised European PhD programme to train statisticians in quantitative methods for drug development.